2018
DOI: 10.1111/add.14249
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence diagnoses among abstainers, low‐risk drinkers and at‐risk drinkers: consideration of the U‐shaped association between alcohol use and sickness absence in four cohort studies

Abstract: AimsTo estimate differences in the strength and shape of associations between alcohol use and diagnosis‐specific sickness absence.DesignA multi‐cohort study. Participants (n = 47 520) responded to a survey on alcohol use at two time‐points, and were linked to records of sickness absence. Diagnosis‐specific sickness absence was followed for 4–7 years from the latter survey.Setting and participantsFrom Finland, we had population cohort survey data from 1998 and 2003 and employee cohort survey data from 2000–02 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Our results that psychosocial working conditions predicted DP differently depending on DP diagnosis group confirms the importance to investigate the diagnosis groups instead of focusing on DP in general [12,13] or only one diagnosis group [10,11]. Furthermore, the assumption that health behaviours would be influential for the pathway to work incapacity in terms of DP [19][20][21][22] was confirmed in our study. In this study, the associations of job control, job demands and social support with DP varied if one had healthy or unhealthy behaviours based on tobacco and alcohol consumption and physical activity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results that psychosocial working conditions predicted DP differently depending on DP diagnosis group confirms the importance to investigate the diagnosis groups instead of focusing on DP in general [12,13] or only one diagnosis group [10,11]. Furthermore, the assumption that health behaviours would be influential for the pathway to work incapacity in terms of DP [19][20][21][22] was confirmed in our study. In this study, the associations of job control, job demands and social support with DP varied if one had healthy or unhealthy behaviours based on tobacco and alcohol consumption and physical activity.…”
Section: Discussionsupporting
confidence: 83%
“…The assumed pathway is that even modest improvement in health behaviours could markedly affect the disease risk and consequently also the risk for DP. Thus, DP is known to be associated with various health behaviours [ 19 – 22 ] as has been also shown by earlier twin studies [ 23 , 24 ]. Since many health behaviours are clustered and various other (i.e.…”
Section: Introductionmentioning
confidence: 72%
“…Available evidence on lifestyle and diagnosis-specific sickness absence is limited to investigations that have assessed one lifestyle factor or one diagnosis outcome at a time, thus preventing comparisons of the relative importance of different lifestyle factors for different diagnostic groups. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Some of these studies have been small in scale (sample size between 200 and 4000 participants) and have provided imprecise estimates. 11 , 12 , 13 , 14 , 17 The overall evidence is characterised by mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 , 17 The overall evidence is characterised by mixed findings. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 48 Other studies found a U-shaped relationship between alcohol consumption and sickness absenteeism such that people who abstained from alcohol had higher sickness absenteeism than people who consumed alcohol moderately. 49 …”
Section: Discussionmentioning
confidence: 99%